Gamma Radiolytic Decomposition of KNO3 in Presence of Aluminium and Its Compounds - Das Sarma , Indrani; Parwate, D.V. (Asian Journal of Chemistry, 2010)
The present work has been carried out to investigate the effect of aluminium and its different compounds on the radiolytic decomposition of potassium nitrate. The radiolytic decomposition of the admixtures has been studied over a range of gamma dose of 1-110 KGy. The amount of nitrite formed was estimated spectrophotometrically. In case of admixtures of aluminium powder and sodium aluminate with potassium nitrate the G values have been found to increase with increase in their mole fractions while in case of admixtures of aluminium oxide and potash alum with potassium nitrate a reverse trend is seen. The increase in G values has been attributed to the transfer of energy absorbed by the additives or vice-versa.